Clinical Outcomes and Radiologic Changes After Microsurgical Bilateral Decompression by a Unilateral Approach in Patients With Lumbar Spinal Stenosis and Grade I Degenerative Spondylolisthesis With a Minimum 3-Year Follow-Up. Issue 7 (August 2016) - Jang, Jun-Won; Park, Jin-Hun; Hyun, Seung-Jae; Rhim, Seung-Chul
Abstract : Study Design: A retrospective study. Objective: To analyze the clinical outcomes and radiologic changes after microsurgical bilateral decompression via a unilateral approach in patients with lumbar spinal stenosis (LSS) and degenerative spondylolisthesis (DS). Summary of Background Data: Satisfactory short-term results have been observed after minimally invasive decompressive procedures, but intermediate-term and long-term outcomes have not been assessed. It is not yet clear whether decompressive laminectomy with concomitant fusion is the optimal surgical treatment for spinal stenosis combined with mild DS. We, therefore, evaluated minimum 3-year clinical outcomes and radiologic changes in patients with LSS and grade 1 DS, who underwent microsurgical bilateral decompression via a unilateral approach, without fusion. Methods: We assessed 21 consecutive patients who underwent surgery conducted by a single surgeon of our hospital, between 2005 and 2007. The Oswestry Disability Index was determined preoperatively, just before discharge, and at last follow-up. Plain dynamic x-rays were used to determine slip percentages. Results: Average patient age and clinical and radiologic follow-up periods were 67 years, 49.3 months, and 18 months, respectively. Preoperative, immediate postoperative, and last follow-up average Oswestry Disability Indices were 59.52±9.00, 50.19±7.23, and 26.19±12.42, respectively. However, 1 patient experienced aggravated symptoms and later underwent a fusion procedure. Of the 22 levels with spondylolisthesis, 15 had no sagittal motion as the difference in slip percentage on dynamic x-rays, but 7 showed sagittal motion. Average slip percentages increased from 13.90±5.41% to 14.60±5.78% for levels without sagittal motion on dynamic x-ray, and from 13.12±3.48% to 18.58±4.55% for levels with sagittal motion. Conclusions: Despite small case series with retrospective design and the absence of a control group, our study suggests that bilateral decompression via a unilateral approach in patients with LSS and grade 1 DS showed good mid-term clinical outcomes, despite an increase in slip percentage. However, more marked increases in slippage were observed in patients with sagittal motion in spondylolisthesis levels on preoperative dynamic x-ray, than in patients without sagittal motion. Therefore, bilateral decompression via a unilateral approach can aggravate symptoms related to instability in patients with preoperative sagittal motion on dynamic x-ray, and needs a longer term follow-up than in our study.